2012
DOI: 10.1161/hypertensionaha.112.190892
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Protein Period 1 Contributes to Blood Pressure Control and Coordinately Regulates Renal Sodium Transport Genes

Abstract: The circadian clock protein Period 1 (Per1) contributes to the regulation of expression of the α subunit of the renal epithelial sodium channel (αENaC) at the basal level and in response to the mineralocorticoid hormone aldosterone. The goals of the present study were to define the role of Per1 in the regulation of additional renal sodium handling genes in cortical collecting duct cells and to evaluate BP in mice lacking functional Per1. To determine if Per1 regulates additional genes important in renal sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
131
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 37 publications
16
131
0
3
Order By: Relevance
“…Per and Cry dimerize and interact with Clock and Bmal1 to repress their transcriptional activity (3,11). Per1 may not act as a canonical repressor, however, as increasing evidence suggests that Per1 may activate gene expression through an unknown mechanism, and this may occur in a tissue-and gene-specific manner (8,16,18,31,36). However, our recent work (30) demonstrated that this possible mechanism could be through repression of the circadian repressor Cry2.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Per and Cry dimerize and interact with Clock and Bmal1 to repress their transcriptional activity (3,11). Per1 may not act as a canonical repressor, however, as increasing evidence suggests that Per1 may activate gene expression through an unknown mechanism, and this may occur in a tissue-and gene-specific manner (8,16,18,31,36). However, our recent work (30) demonstrated that this possible mechanism could be through repression of the circadian repressor Cry2.…”
mentioning
confidence: 93%
“…Surprisingly, no changes were observed in the expression of the aldosterone synthase gene (CYPB11), which encodes the ratelimiting step of aldosterone production. We (16,18,31,36) have previously shown that Per1 regulates both the basal and aldosterone-mediated regulation of the ␣-subunit of the renal epithelial Na ϩ channel (␣-ENaC). We (26) have also demonstrated that Per1 coordinately regulates the expression of multiple genes that contribute to the regulation of renal Na ϩ reabsorption.…”
mentioning
confidence: 99%
“…Similar relationships between systolic BP and a J-shaped relationship for diastolic BP have been demonstrated in patients receiving maintenance hemodialysis, as well as in patients with less advanced CKD who do not require dialysis. 12,13 In the absence of aortic valve insufficiency, the pattern of high systolic BP, low diastolic BP, and increased pulse pressure are a marker of vascular stiffness. This has been extensively studied in CKD and ESRD, and it reflects accelerated arteriosclerosis and vascular calcification in progressive renal disease.…”
Section: Nonementioning
confidence: 99%
“…8,9 Consistent with these mechanistic molecular findings in renal models, studies in circadian KO mice have consistently demonstrated a role for each of the core clock proteins in BP control. [10][11][12][13] An important role for the kidney in these BP phenotypes has often been proposed, but the lack of renal cell type-specific KO models of circadian genes has prevented the use of a genetic model to directly test this hypothesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation